1994
DOI: 10.1007/bf00193126
|View full text |Cite
|
Sign up to set email alerts
|

The growth of long bones in human embryological and fetal upper limbs and its relationship to other developmental patterns

Abstract: Measurements were made of the long bones of the upper limbs (humerus, ulna, radius) of 58 aborted embryos and fetuses, developmental age from 8 to 14 weeks, crown-rump length (CRL) between 38 and 116 mm. The specimens were cleared and double-stained, using alcian blue and alizarin red S for a differential detection of cartilage and bone. The values of both the total length (TL) and the ossified part (OL) of each long bone were related to the fetal developmental age previously estimated by freshly measured CRL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
(17 reference statements)
1
19
0
2
Order By: Relevance
“…Studies of individuals of similar age to the current work support the observation that asymmetry becomes increasingly right-sided during growth (Van Dusen, 1939;Ingelmark, 1946;Steele and Mays, 1995). Although some previous research has found right-sided asymmetry early in development, much of that work is based on prenatal samples (Schultz, 1926;Pande and Singh, 1971;Bareggi et al, 1994). This could suggest that shifts in asymmetry occur between embryonic development, birth, and the first several months of life.…”
Section: Discussionsupporting
confidence: 83%
“…Studies of individuals of similar age to the current work support the observation that asymmetry becomes increasingly right-sided during growth (Van Dusen, 1939;Ingelmark, 1946;Steele and Mays, 1995). Although some previous research has found right-sided asymmetry early in development, much of that work is based on prenatal samples (Schultz, 1926;Pande and Singh, 1971;Bareggi et al, 1994). This could suggest that shifts in asymmetry occur between embryonic development, birth, and the first several months of life.…”
Section: Discussionsupporting
confidence: 83%
“…Some researchers have hypothesized that subtle asymmetries in length may be linked to bilateral differences in blood oxygen levels, potentially leading to unequal bone growth [Steele, 2000a, b]. Such innate factors would also help explain why, according to some research, human foetuses already exhibit heavier muscle and bone weights as well as greater lengths on the right arm in utero [Pande and Singh, 1971;Bareggi et al, 1994]. Other studies, however, have failed to confirm these patterns or even found the opposite to be the case, and more research will be needed to establish whether consistent biases already exist at foetal stages [Steele, 2000a, b].…”
Section: Humeral Length Asymmetries In Humans and African Apesmentioning
confidence: 99%
“…However, because humans show relatively little bilateral asymmetry in humeral lengths compared to other features, such as cross-sectional geometry [Trinkaus et al, 1994;Auerbach and Ruff, 2006], some uncertainty exists about whether these occur as a consequence of mechanical stimuli or of intrinsic genetic/ hormonal factors, and therefore whether they can be linked to behavioural lateralization at all [Jolicoeur, 1963;Stirland, 1993;Trinkaus et al, 1994;Steele and Mays, 1995]. The presence of length asymmetries in human foetuses [Pande and Singh, 1971;Bareggi et al, 1994] suggests that this may be the case, but ultrasound evidence also indicates that 85% of human foetuses at 10 weeks of gestational age move their right arm more than their left arm [Hepper et al, 1998;Steele, 2000b], raising the possibility that, although partly congenital, asymmetries in humeral length may be further enhanced by preferential use of the right arm, which may commence early in development and continue throughout growth [Stirland, 1993]. It is unclear, however, whether this pattern is unique to humans or whether it is shared with African apes.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that different growth factors exist between the ossified part and the cartilage part of the fetal long bones. Bareggi et al (1994) pointed out that the total length of long bones including the cartilage part may provide debatable information relevant to an assessment of fetal age compared with the use of the ossified diaphyseal length. Our results indicated that an independent variation existed in the cartilage part of long bones and supported their opinion.…”
Section: Discussionmentioning
confidence: 99%